1994
DOI: 10.1029/94gl02481
|View full text |Cite
|
Sign up to set email alerts
|

Climatic impact of the A.D. 1783 Asama (Japan) Eruption was minimal: Evidence from the GISP2 Ice Core

Abstract: Assessing the climatic impact of the A.D. 1783 eruption of Mt. Asama, Japan, is complicated by the concurrent eruption of Laki, Iceland. Estimates of the stratospheric loading of H2SO4 for the A.D. 1108 eruption of Asama derived from the SO42− time series in the GISP2 Greenland ice core indicate a loading of about 10.4 Tg H2SO4 with a resulting stratospheric optical depth of 0.087. Assuming sulfur emissions from the 1783 eruption were only one‐third of the 1108 event yields a H2SO4 loading value of 3.5 Tg and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Although Mount Asama in Japan had also erupted violently in August 1783, this explosion left no significant trace in polar ice, and therefore its influence on the Northern Hemisphere's weather may be doubted (Zielinski et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although Mount Asama in Japan had also erupted violently in August 1783, this explosion left no significant trace in polar ice, and therefore its influence on the Northern Hemisphere's weather may be doubted (Zielinski et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It is more likely that the cooling events are due to suppressed solar activity from the 1790s to 1820s (Dalton Minimum), which also coincides with global cooling [e.g., Ruzmaikin et al, 2004]. Although Zielinski et al [1994] concluded that an eruption of Asama (central Japan) in the same year as Laki did not affect the global climate, regional historical records revealed that ash fall and unusual 'dry fogs' in August subsequent to the bad crop in the previous year devastated the societal conditions seriously at that time [e.g., Hayakawa and Nakajima, 1998]. The cooling events identified as our periods II and III support this historical episode.…”
Section: Historical Notesmentioning
confidence: 99%
“…Briffa et al (1998) found changes in tree rings which indicated a Northern Hemisphere mean temperature anomaly of −0.27 • C (±0.3 • C being the 95% confidence limits of this change). However, Zielinski et al (1994) assert that Asama probably had little climatic impact based on previous eruptions; perhaps this was because Asama eruptions generally do not release much sulphur (Kohno et al, 1993). This eruption may, however, account for reports of a cold wet summer in Japan during 1783 (Mikami, 1987).…”
Section: Introductionmentioning
confidence: 99%